Unveiling Motivations Behind Eco-Conscious Choices for Sustainable Cookware - Jamal, Farkhan Najisurya; Kasmo, Arief Bowo Prayoga (International Journal of Indonesian Business Review, 2025)
Purpose – The increasing health and environmental awareness among customers has drastically influenced their buying habits, particularly related to the cookware industry. This research is carried out to investigate the relation of environmental knowledge, environmental concern, and eco-label with purchase intention toward sustainable cookware products. Methodology/approach – Quantitative techniques were used in this study, gathering responses from 175 participants chosen through purposive sampling technique. Data analysis was performed using the PLS-SEM approach. Findings – Research indicates environmental knowledge shows no discernible and significant effect in shaping consumers’ purchase intention. There is a significant and favorable influence on purchase intention from both environmental concern and eco-label. These results emphasise the significance of environmental values and credible product labeling in influencing consumers’ intentions to purchase sustainable cookware.